2011
DOI: 10.1186/1471-2393-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid function and the outcome of external cephalic version: a prospective cohort study

Abstract: BackgroundTo investigate the relation between maternal thyroid function and the outcome of external cephalic version (ECV) in breech presentation.MethodsProspective cohort study in 141 women (≥ 35 weeks gestation) with a singleton fetus in breech. Blood samples for assessing thyroid function were taken prior to ECV. Main outcome measure was the relation between maternal thyroid function and ECV outcome indicated by post ECV ultrasound.ResultsECV success rate was 77/141 (55%), 41/48 (85%) in multipara and 36/93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…ECV performed at early gestation seems to influence the success rate indirectly through adequacy of liquor volume and nonengagement of presenting part as shown by Aisenberry et al 13 In our study, BMI was found to be one of the strongest determinants of ECV success as reported by Ben Mier et al, 11 while some authors have used ease of palpation of fetal head as an indirect assessment of BMI. 5,13 Similarly, positive association of flexed breech with success of ECV has been reported in many studies previously, 4,10,12 which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…ECV performed at early gestation seems to influence the success rate indirectly through adequacy of liquor volume and nonengagement of presenting part as shown by Aisenberry et al 13 In our study, BMI was found to be one of the strongest determinants of ECV success as reported by Ben Mier et al, 11 while some authors have used ease of palpation of fetal head as an indirect assessment of BMI. 5,13 Similarly, positive association of flexed breech with success of ECV has been reported in many studies previously, 4,10,12 which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 83%
“…This was similar to that reported by Hutton et al (49.1%) 9 and Kuppens et al (55%). 10 The success rate in local studies varies from 47 to 67.5% while that in international studies is quoted from 48 to 77%. 7 Our study showed that both scoring systems had significant correlation with success of ECV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta‐analysis showed a significantly increased risk of prematurity (OR 1·3; 95% CI: 1·05–1·60) and placental abruption (OR 2·16; 95% CI: 1·15–4·06), which could be factors mediating the poor perinatal outcomes associated with subclinical hypothyroidism. Circulating TSH concentrations >95th centile at 36 weeks have also been associated with breech presentation (Table B) and a reduced external cephalic version success rate …”
Section: Subclinical Hypothyroidismmentioning
confidence: 99%
“…2 Furthermore, in a separate study, the same group has also shown that high serum TSH is associated with an increased risk of failure of external cephalic version (ECV) in women with breech presentation. 3 However, the association between breech presentation and maternal hypothyroidism needs replication in other populations. Therefore, we aimed to assess, in a UK population, whether there is an increased prevalence of thyroid dysfunction in women presenting with a breech position in late gestation.…”
Section: Maternal Thyroid Function In Pregnant Women With a Breech Prmentioning
confidence: 99%